Model Komunikasi Persuasif dalam Perspektif Al-Qur’an sebagai Metode Dakwah Nabi Ibrahim as - Suaib Zainal (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2015)
Among the many methods of Da'wah is by verbal communication. Communication becomes a mean to convey the message of da'wah to mad'u. But not every communication will be accepted or will perceived by the mad’u. That is why the communication in the Qur'an always applied a persuasive preaching. Communication made by Prophet Ibrahim in preaching to his father and his people, and the king at that time is always in a persuasive manner. Even when his father angry, he still pray and hope that his father gets guidance. Among the communication model contained in the Qur'an is Qawlan Sadida, Qawlan Ma'rufa, Qawlan Baligha, Qawlan Maysura, Qawlan Layyina, Qawlan Karima.